In situ observation of the evolution of polyaromatic tar precursors in packed-bed biomass pyrolysis. Issue 9 (30th May 2021) - Chelang'at Mosonik, Maryanne; Volpe, Roberto; Ezenwajiaku, Chinonso; Talibi, Midhat; Balachandran, Ramanarayanan
Abstract : In situ planar laser-induced fluorescence (PLIF) shows the effects of pyrolysis peak temperature and holding time on the formation of 3–5 rings polyaromatic hydrocarbons (PAHs) in the vapour phase during pyrolysis of biomass samples. Abstract : Pyrolysis provides a route for the conversion of lignocellulosic biomass into solid, liquid and gaseous energy vectors or platform chemicals. Polycyclic aromatic hydrocarbons (PAHs) generated in the vapour phase of the biomass pyrolytic reaction may condense to form tars, which are difficult to further upgrade and cause process inefficiency. Control of tar production requires optimization of reactor design and careful control of reactor operating conditions. In this study, a vertical resistively-heated fixed-bed reactor is used to study the effect of pyrolysis peak temperatures and holding period (at peak temperature) on the formation of PAHs during pyrolysis of two lignocellulosic biomass samples, walnut shells (WS) and almond shells (AS). ' In situ ' planar laser induced fluorescence (PLIF) is used to optically detect 3-to-5 ring PAHs in the vapour phase immediately above the reactor bed. Results show that the PAH PLIF signal appeared at ∼275 °C for the biomass samples and peaked at ∼400 °C for WS and ∼375 °C for AS, which is in agreement with previous ' off situ ' analysis conducted by the authors. Beyond 400 °C, the PLIF signal was observed to reduce significantly and almost disappear at 550 °C. Initial PAH formation was attributed to condensation reactions occurring due to the drop in temperature along the sample bed. The detection of the PAH PLIF signal itself and its changing intensities, close to the bed, signified the rapid changes the products released from biomass undergo and emphasised the importance of using online techniques for pyrolysis studies. The detailed understanding of the temperature dependent characteristics of PAH formation from this study could help improve reactor design.